2022
DOI: 10.1177/17085381221097746
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in long-term outcomes of patients with deep vein thrombosis

Abstract: Objective Sex differences in short-term outcomes of patients with deep vein thrombosis (DVT) have been reported, but differences in long-term outcomes remain poorly characterized. This study aimed to evaluate sex differences in long-term mortality, venous thromboembolism (VTE)-related mortality, and bleeding-related mortality in patients with DVT at a tertiary care center. Methods A retrospective chart review from 2012 to 2018 of all consecutive patients diagnosed with DVT was performed. Patients were grouped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…It is unclear to what extent this generalizes specifically to VTEs: One study of DVT events found more women than men were sent for a diagnostic workup for DVT, but the actual diagnosis of DVT was higher in men with more severe thrombotic events ( 68 ). However, women have poorer quality-of-life outcomes 1 year after diagnosis ( 69 ), worse bleeding outcomes, and more VTE mortality in long-term follow-up ( 70 ). Given this, the magnitude of the impact of sex bias on VTE reporting is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear to what extent this generalizes specifically to VTEs: One study of DVT events found more women than men were sent for a diagnostic workup for DVT, but the actual diagnosis of DVT was higher in men with more severe thrombotic events ( 68 ). However, women have poorer quality-of-life outcomes 1 year after diagnosis ( 69 ), worse bleeding outcomes, and more VTE mortality in long-term follow-up ( 70 ). Given this, the magnitude of the impact of sex bias on VTE reporting is uncertain.…”
Section: Discussionmentioning
confidence: 99%